Membangun Karakter Kebersamaan Siswa Melalui Permainan Angklung - Sucipto, Sucipto (Jurnal Global Ilmiah, 2025)
This study aims to analyze the effectiveness of angklung playing in building the character of togetherness among sixth-grade students at SDN Junrejo 02 Batu City. Angklung as a traditional Indonesian musical instrument that applies the philosophy of "one angklung one note" has great potential in developing students' cooperation and solidarity abilities. This study uses a qualitative approach with descriptive methods involving 55 sixth-grade students during one semester of learning. Data collection techniques were carried out through observation, interviews with arts and culture teachers and students, as well as documentation of angklung learning activities. Data validity was obtained through source triangulation to ensure information accuracy. The results showed that angklung playing is effective in fostering students' character of togetherness through the development of collective responsibility, communication skills, and tolerance within the team. Despite facing challenges such as tempo inaccuracy and coordination issues, these actually became learning opportunities to improve collaborative problem-solving abilities. Students were able to play four songs in one semester with good coordination after going through gradual and repeated practice with piano music guidance. The positive impact of angklung learning also carries over into students' social interactions outside musical activities, demonstrating sustainable togetherness character. This study concludes that angklung can be an effective medium for building adaptive and sustainable togetherness character in character education at elementary schools.